Three-field versus two-field lymphadenectomy in transthoracic oesophagectomy for oesophageal squamous cell carcinoma: short-term outcomes of a randomized clinical trial. Issue 6 (28th February 2020) - Li, B; Hu, H; Zhang, Y; Zhang, J; Miao, L; Ma, L; Luo, X; Zhang, Y; Ye, T; Li, H; Li, Y; Shen, L; et al.
Abstract: Background: The benefit and harm of three-field lymphadenectomy for oesophageal cancer are still unknown. The aim of this study was to compare overall survival and morbidity and mortality between three- and two-field lymphadenectomy in patients with oesophageal squamous cell carcinoma. Methods: Between March 2013 and November 2016, patients with squamous cell carcinoma of the middle or distal oesophagus were assigned randomly to open oesophagectomy with three-field (cervical–thoracic–abdominal) or two-field (thoracic–abdominal) lymphadenectomy. No chemo(radio) therapy was given before surgery. This paper reports on the secondary outcomes of the study: pathology and surgical complications. Results: Some 400 patients were randomized, 200 in each group. A median of 37 (i.q.r. 30–49) lymph nodes were dissected in the three-field group, compared with 24 (18–30) in the two-field group ( P < 0·001). Some 43 of 200 patients (21·5 per cent) in the three-field group had cervical lymph node metastasis. More patients in the three-field group had pN3 disease: 21 of 200 (10·5 per cent) versus 10 of 200 (5·0 per cent) ( P = 0·040). The rate and severity of postoperative complications were comparable between the two groups, except that six patients in the three-field arm needed reintubation compared with none in the two-field group (3·0 versus 0 per cent; P = 0·030). The 90-day mortality rate was 0 per cent in the three-field group and 0·5 per cent (1 patient) in the two-field group ( P = 1·000). Conclusion: Oesophagectomy with three-field lymphadenectomy increased the number of lymph nodes dissected and led to stage migration owing to a 21·5 per cent rate of cervical lymph node metastasis. Postoperative complications were largely comparable between two- and three-field lymphadenectomy. Registration number: NCT01807936 (https://www.clinicaltrials.gov ). Graphical Abstract: The optimal extent of lymphadenectomy for oesophageal squamous cell carcinoma remains unclear. This trial randomized 400 patients with middle and lower thoracic oesophageal cancer to receive oesophagectomy with two- or three-field lymphadenectomy. In the present analysis based on short-term outcomes, three-field lymphadenectomy could also be performed safely, offering more accurate nodal staging with a 21·5 per cent incidence of unforeseen cervical lymph node metastases. Difference in nodal yield, survival awaited for